AN ANALYSIS OF GRAMMATICAL ERRORS IN STATUS AND CHATTING AMONG ENGLISH TEACHERS THROUGH WHATSAPP MESSENGER - Asri Zulbeni (English Language Teaching and Research, 2017)
Internet is the most well-known medium in new digital era, with the technology Web 2.0, allows people to produce a content in the internet. For example, Sosial Networking Sites (SNS) as a new path in building networks with other people allows user to interact each other through the Internet. Among social media users in Indonesia, For messenger or chat applications category of a survey done by globalwebindex.net, WhatsApp was on the first position in 2016. The current study will be aimed at identify, classify, analyze, and describe the English teacher grammatical errors during their status and daily conversation in the application, WhatsApp messenger application, in that up to this present time there is no-publicly work in Indonesia that analyze the grammatical use of EFL teachers whether they are certified or uncertified based on Indonesian teacher’s policy, in practicing English on chatting and updating status through WhatsApp. This present study will be conducted to answer one central question: How do English teachers use grammar correctly through WhatsApp messenger application? The objectives of the current study are: to identify and describe the grammatical errors of certified and uncertified English teachers made during updating status, chatting, through WhatsApp messenger and to explore information from English teachers about the grammatical errors that they made while using WhatsApp messenger application. Key words: WhatsApp messenger, English teachers, Grammatical error.